2017
DOI: 10.17645/mac.v5i3.989
|View full text |Cite
|
Sign up to set email alerts
|

Raging Against the Machine: Network Gatekeeping and Collective Action on Social Media Platforms

Abstract: Social media platforms act as networked gatekeepers-by ranking, channeling, promoting, censoring, and deleting content they hold power to facilitate or hinder information flows. One of the mechanisms they use is content moderation, or the enforcement of which content is allowed or disallowed on the platform. Though content moderation relies on users' labor to identify content to delete, users have little capacity to influence content policies or enforcement. Despite this, some social media users are turning to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
2
26
0
Order By: Relevance
“…Nor is this something necessarily new. Merrit Roe Smith argues that the belief in technological determinism dates back to the industrial revolution at least, an assumption whose European roots grew more deeply in America so that by the early twentieth century, advertisers and industrialists "quickly mastered the idea of the technological fix" 33 The folly of Zuckerberg's particular technological fix in the light of the presidential election of 2016 will be the subject of a later chapter, but it is also worth commenting on that he suffers from this misconception of technology as separate to society, to history, as something outside which operates on culture and human behaviour, the billiard ball which can ricochet us into the right pocket if only we can control the levers of that technology. As Nicholas Carr correctly observes, Zuckerberg can only entertain the notion of a planetary community because he fundamentally misunderstands what community means, that communities nearly always comprise groups of individuals who have found a way to get along despite sometimes fundamental differences of opinion and belief, or which, as in the case of religious communities, may be oppositional to the communities in which they find themselves.…”
Section: Digital Ecosystems Media Ecologies and Technological Determentioning
confidence: 99%
See 4 more Smart Citations
“…Nor is this something necessarily new. Merrit Roe Smith argues that the belief in technological determinism dates back to the industrial revolution at least, an assumption whose European roots grew more deeply in America so that by the early twentieth century, advertisers and industrialists "quickly mastered the idea of the technological fix" 33 The folly of Zuckerberg's particular technological fix in the light of the presidential election of 2016 will be the subject of a later chapter, but it is also worth commenting on that he suffers from this misconception of technology as separate to society, to history, as something outside which operates on culture and human behaviour, the billiard ball which can ricochet us into the right pocket if only we can control the levers of that technology. As Nicholas Carr correctly observes, Zuckerberg can only entertain the notion of a planetary community because he fundamentally misunderstands what community means, that communities nearly always comprise groups of individuals who have found a way to get along despite sometimes fundamental differences of opinion and belief, or which, as in the case of religious communities, may be oppositional to the communities in which they find themselves.…”
Section: Digital Ecosystems Media Ecologies and Technological Determentioning
confidence: 99%
“…As Fortunati and O'Sullivan observe, print newspapers have come to be seen as the "weakest layer" in the network of personal media, which has important consequences for social participation and sustainable social change. 33 The impact of digital technologies on legacy news media, whether the web or mobile, has been well-documented over the past decade or more. The Pew Research Center data previously reported that between 2003 and 2014, circulation numbers in the United States were down 27 per cent, with a 35 per cent decline in reporters.…”
Section: The Decline Of Legacy Mediamentioning
confidence: 99%
See 3 more Smart Citations